2006
DOI: 10.1111/j.1442-2042.2006.01388.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of frozen sections of lymph nodes in pelvic lymphadenectomy in patients with invasive bladder tumor

Abstract: Aim : We examined the reliability of classical lymph node evaluation methods. We compared the results of preoperative computed tomography (CT) and perioperative frozen section examination of lymph nodes in patients on whom radical cystectomy was performed because of invasive bladder tumors. Methods : A total of 142 patients, in whom radical cystectomy was performed because of invasive bladder tumors between the years 1994 and 2005 in our clinic, and 284 pelvic lymph node regions were evaluated retrospectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…22 Ugurlu et al found similar performance characteristics of frozen section analysis in assessing multiple nodal regions, reporting a sensitivity of 81% and a specificity of 100%. 23 They and others have suggested that an extended template dissection may be used only in patients with lower echelon lymph nodes that are positive on frozen section. 10 Baltaci et al proposed using clinical staging information as well since they found no false-negatives on frozen section analysis when limiting to patients with less than clinical stage T2 disease.…”
Section: Alternative Approachesmentioning
confidence: 99%
“…22 Ugurlu et al found similar performance characteristics of frozen section analysis in assessing multiple nodal regions, reporting a sensitivity of 81% and a specificity of 100%. 23 They and others have suggested that an extended template dissection may be used only in patients with lower echelon lymph nodes that are positive on frozen section. 10 Baltaci et al proposed using clinical staging information as well since they found no false-negatives on frozen section analysis when limiting to patients with less than clinical stage T2 disease.…”
Section: Alternative Approachesmentioning
confidence: 99%
“…perioperative FS examination of external iliac, hypogastric, and obturator lymph nodes during radical cystectomy with the intention to limit PLND has been investigated in several studies (70)(71)(72)(73). In a multicenter study, Adsan et al tested the reliability of frozen section examination of external iliac, hypogastric, and obturator lymph nodes during radical cystectomy.…”
Section: Frozen Section (Fs)mentioning
confidence: 99%